Análisis molecular de la γ-kafirina en variedades de sorgo blanco (Sorghum bicolor) - Chiquito Almazán, Elizabeth (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
The use of sorghum seed in animal feed is limited by its low digestibility, caused by tannin content and the formation of oligomers kafirins, a family of hydrophobic prolaminas classified α, β, γ and δ-kafirins. The γ-kafirins could participate in reducing digestibility form disulfide bonds. They have reported two γ-kafirin sequences with 99% identity in the putative amino acid sequence, of genomic DNA (no. X62480 access) and another cDNA (no. M73688 access). But it is unknown whether there are differences in amino acid sequence between white sorghum materials. This study aimed to determine the electrophoretic profile prolaminas, the content of γ-kafirin, and the putative amino acid sequence of γ-kafirin in 12 white sorghum materials. The electrophoretic profile of kafirins was obtained under denaturing polyacrylamide gels (SDS-PAGE). The content of g-kafirin was obtained by densitometric quantification of the band. The coding region gene-kafirin g was obtained by PCR using genomic DNA and the amplification product was used to determine the nucleotide sequence, from which the amino acid sequence was deduced. The secondary and tertiary structure of the g-kafirin was obtained by in silico analysis based on the amino acid sequence. A71 material showed the lowest digestibility in vitro with pepsin (76.6%), while the Var-9 the highest (87.4%) (P <0.05) material. The electrophoretic profile in the 12 kafirins materials showed the presence of α1, α2, β, and γ- kafirins. Although no significant differences γ-kafirin higher content material were detected in the content was A71 (5.19%) and the lowest was A20 (2.76%).

El uso de la semilla del sorgo en la alimentación animal está limitado por su baja digestibilidad, causada por el contenido de taninos y la formación de oligómeros de kafirinas, una familia de prolaminas hidrofóbicas clasificadas en α, β, γ y δ-kafirinas. Las γ-kafirinas podrían participar en la disminución de la digestibilidad formando enlaces disulfuro. Se han reportado dos secuencias de γ-kafirina con un 99% de identidad en la secuencia putativa de aminoácidos, una de ADN genómico (no. acceso X62480) y otra de ADNc (no. acceso M73688). Pero se desconoce si existen diferencias en la secuencia de aminoácidos entre materiales de sorgo blanco. Este trabajo tuvo como objetivo determinar el perfil electroforético de prolaminas, el contenido de γ-kafirina, y la secuencia putativa de aminoácidos de γ-kafirina en 12 materiales de sorgo blanco. El perfil electroforético de las kafirinas se obtuvo en geles desnaturalizantes de poliacrilamida (SDS-PAGE). El contenido de g-kafirina se obtuvo por cuantificación densitométrica de la banda. La región codificante del gen de g-kafirina se obtuvo por PCR usando ADN genómico y el producto de amplificación se utilizó para determinar la secuencia de nucleótidos, a partir de la cual se dedujo la secuencia de aminoácidos. La estructura secundaria y terciaria de la g-kafirina se obtuvo por análisis in silico, a partir de la secuencia de aminoácidos. El material A71 mostró la menor digestibilidad in vitro con pepsina (76.6%), mientras que el material Var-9 la más alta (87.4%) (P<0.05). El perfil electroforético de kafirinas en los 12 materiales mostró la presencia de α1, α2, β, y γ- kafirinas. Aunque no se detectaron diferencias significativas en el contenido de γ-kafirina el material de mayor contenido fue A71 (5.19%) y el de menor fue A20 (2.76%).
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FMVZ-M-2011-0018; Análisis molecular; Agricultura; Sorgo blanco; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1928